De novo donor‐specific HLA antibodies after combined intestinal and vascularized composite allotransplantation — a retrospective study. (14th December 2017) - Weissenbacher, Annemarie; Vrakas, Georgios; Chen, Mian; Reddy, Srikanth; Allan, Philip; Giele, Henk; Barnardo, Martin C.N.M; Vaidya, Anil; Friend, Peter J.; Fuggle, Susan V.
Summary: Combining vascularized composite allotransplantation (VCA) with intestinal transplantation to achieve primary abdominal closure has become a feasible procedure. Besides facilitating closure, the abdominal wall can be used to monitor intestinal rejection. As the inclusion of a VCA raises the possibility of an enhanced alloimmune response, we investigated the incidence and clinical effect of de novo donor‐specific HLA antibodies (dnDSA) in a cohort of patients receiving an intestinal transplant with or without a VCA. The sequential clinical study includes 32 recipients of deceased donor intestinal and VCA transplants performed between 2008 and 2015; eight (25%) modified multivisceral transplants and 24 (75%) isolated small bowel transplants. A VCA was used in 18 (56.3%) cases. There were no episodes of intestinal rejection without VCA rejection. Fourteen patients (14 of 29; 48.3%) developed dnDSA. In the VCA group, fewer patients developed dnDSA; six of 16 (37.5%) VCA vs. eight of 13 (61.5%) non‐VCA. There was no statistically significant difference in one‐ and 3‐year overall graft survival stratified for the presence of dnDSA; P = 0.286. In the study, there is no evidence that the addition of a VCA increases the incidence of dnDSA formation compared to transplantation of the intestine alone.